Monitor de WhatsApp: Um Sistema para Checagem de Fatos no Combate à Desinformação - Melo, Philipe; Benevenuto, Fabrício; Kansaon, Daniel; Mafra, Vitor; Sá, Kaio (Anais Estendidos do Simpósio Brasileiro de Sistemas Multimídia e Web (WebMedia), 2021)
WhatsApp is the most popular instant messaging application in many countries such as Brazil, India, and Indonesia, where many people use it as the main interface to the Web. Recently, WhatsApp has been pointed as an important actor in the spreading of misinformation. However, due to its encrypted and peer-to-peer nature, it is hard for people to explore the content people share within WhatsApp at scale. In this work, we propose the Monitor de WhatsApp ( http://www.whatsapp-monitor.dcc.ufmg.br/ ), a web-based system that helps researchers and journalists explore the nature of content shared on WhatsApp public groups from three different contexts: Brazil, India, and Indonesia. Our tool monitors multiple content categories such as images, videos, audio, and textual messages posted on a set of WhatsApp groups and displays the most shared content ranked per day. Our tool has been used for monitoring content during the 2018 Brazilian Elections to the COVID-19 pandemics and was one of the major sources for estimating the spread of misinformation and helping fact-checking efforts on WhatsApp scenario.